COLD REGIONS SCIENCE AND ENGINEERING MONOGRAPH 3, SECTION C5b: SEWERAGE AND SEWAGE DISPOSAL IN COLD REGIONS - Alter,Amos J. (1969)
The main items dealt with in the monograph are: practice and problems, collection and transport, treatment and processes, thermology, re-use and regenerative processes, and construction and operation. (Author)